A ANALYSIS OF THE INFLUENCE OF THE NUMBER OF SERVICE FILE SUBMISSIONS FOR THE RP0.00 TARIFF AND INFLATION ON NON-TAX STATE REVENUE (NTSR) PERFORMANCE AT THE MINISTRY OF AGRARIAN AFFAIRS AND SPATIAL PLANNING/NATIONAL LAND AGENCY: English - Latif Sholichin; Prabawa Eka Soesanta; Lela Nurlaela Wati (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2026)
This study is motivated by the need to improve the accuracy of planning and forecasting Non‑Tax State Revenue (NTSR) within the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency, particularly because sectoral policy dynamics and macroeconomic conditions often influence revenue patterns. Previous research has generally focused on the technocratic aspects of NTSR management without thoroughly examining how service policies—especially services with a tariff of Rp0.00—interact with macroeconomic variables. To fill this gap, the present study aims to analyze the effect of the volume of applications for Rp0.00‑tariff services, as a representation of sectoral policy, and inflation as a macroeconomic indicator, on NTSR performance. The research employs a Sequential Explanatory Mixed Methods design, beginning with a quantitative time‑series analysis for the period 2018–2023 using multiple linear regression, followed by semi‑structured interviews to provide deeper explanations for the numerical findings. The results indicate that Rp0.00‑tariff services have a significant impact on NTSR performance, while inflation does not exert a meaningful influence. Qualitative evidence confirms that the Rp0.00 tariff policy functions as a catalyst for demand for derivative land services, whereas inflationary pressures do not affect the public’s propensity to apply for land‑related services.